Enhancing cracking resistance in semi-flexible pavements using an interfacial immersion method - Xiaoyu Liu; Kuanghuai Wu; Giovanni Giacomello; Yunpeng Yue; Fengming Ren; Xu Cai; Marco Pasetto (Case Studies in Construction Materials)
Semi-flexible pavement (SFP) is a composite structure that combines an asphalt mixture skeleton with cementitious grout, providing excellent load-bearing capacity and rutting resistance. However, cracking is a primary failure mode in SFP, due to the numerous asphalt-grout interfaces within SFP. To enhance the cracking resistance of SFP, an interfacial immersion method is proposed to immerse the porous asphalt mixture (PAM) specimens using a silane coupling agent (SCA) in this paper. Compared to traditional methods. this method directly improves the crack resistance of SFP by strengthening the interface. Three strengths of grout materials were applied to investigate the cracking resistance of SFP through the dynamic modulus and four-point bending fatigue tests after the interface modification. Experimental results indicate that the proposed interfacial immersion method can improve the stiffness performance of SFP, with specimens treated with an interface modifier showing a higher dynamic modulus. Temperature changes significantly affect the stiffness of the SFP when below 20°C, whereas frequency changes have a lesser impact on stiffness especially at low frequencies. Compared to SFP specimens made with high-strength grout materials, those formed with low-strength grout materials showed a superior fatigue life after interfacial modification. The proposed immersion method increased the cracking resistance parameters of SFP by 4.7 % and 11.5 % for GM-40 and GM-60 grouts, respectively, while reducing it by 38 % for GM-70 grout. The fatigue life of the SFP material formed by the GM-40, GM-60, and GM-70 grout material increased by 251.1 %, 18.5 %, and 10.9 % after the interface was enhanced, respectively. It indicates that the crack resistance of SFP formed with low-strength grout materials is significantly enhanced after interface modification using the proposed method. The results will enhance the cracking resistance and durability of SFP, providing support for SFP design.